2013
DOI: 10.3762/bjnano.4.104
|View full text |Cite
|
Sign up to set email alerts
|

STM tip-assisted engineering of molecular nanostructures: PTCDA islands on Ge(001):H surfaces

Abstract: SummaryIslands composed of perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) molecules are grown on a hydrogen passivated Ge(001):H surface. The islands are studied with room temperature scanning tunneling microscopy and spectroscopy. The spontaneous and tip-induced formation of the top-most layer of the island is presented. Assistance of the scanning probe seems to be one of the factors that facilitate and speed the process of formation of the top-most layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The island edges, height and general morphology all are preserved. However, we have found that there is a possibility to interact with such a stable nanocrystal through the change in scanning conditions [20]. Indeed, by applying voltage pulses in the vicinity or on the top of the island a dynamic process leading to formation on new on-top molecular layer is initiated.…”
Section: Stability Of the Islandsmentioning
confidence: 99%
See 4 more Smart Citations
“…The island edges, height and general morphology all are preserved. However, we have found that there is a possibility to interact with such a stable nanocrystal through the change in scanning conditions [20]. Indeed, by applying voltage pulses in the vicinity or on the top of the island a dynamic process leading to formation on new on-top molecular layer is initiated.…”
Section: Stability Of the Islandsmentioning
confidence: 99%
“…Actually, if there is no STM tip development of the new layer may be even one order of magnitude slower [20]. It must be stated clearly; once the process of growth is started by the pulse it may proceed without the assistance of scanning probe.…”
Section: Stability Of the Islandsmentioning
confidence: 99%
See 3 more Smart Citations